PENGARUH LINGKUNGAN SOSIAL, GAYA HIDUP HEDONISME TERHADAP PERILAKU KEUANGAN MAHASISWA UNIVERSITAS SINGAPERBANGSA KARAWANG - Salma Amelia; Dailibas (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
The purpose of this study is to identify and analyze the influence of the social environment on financial behavior and to identify and analyze the influence of a hedonistic lifestyle on financial behavior. This study uses an associative approach in order to determine the relationship between each variable. The information presented is quantitative in nature, that is, the data is tested and analyzed by counting numbers. The subjects of this study were active students currently studying at Singaperbangsa University, Karawang with a total of 40 respondents. Data were collected by questionnaire and analyzed by multiple linear analysis and hypothesis testing using IBM SPSS 26. The results showed that the social environment had a significant effect on financial behavior and the hedonism lifestyle did not have a significant effect on financial behavior.